The Influence of Green Marketing Attitude Environment Awareness and Health on Purchasing Decisions for Somethinc Product - Rakhayu; Herni Justiana Astuti (International Journal of Educational and Life Sciences, 2024)
This research aims to analyze the influence of green marketing, attitudes, environmental awareness and health on purchasing decisions for certain products. The data source used in this research is primary data obtained using data collection techniques by distributing questionnaires using Google Form. The method in this research uses SEM (Structural Equation Model) with the PLS (Partial Least Square) version 3.0 approach. The number of samples tested was 118 respondents. The sampling technique used purposive sampling. The research results show that attitude, environmental awareness and health have a positive and significant effect on purchasing decisions, but green marketing has no effect on purchasing decisions. The managerial implications that can be given are that companies need to re-evaluate green marketing, increase their focus on understanding consumer attitudes and must continue to increase environmental and health awareness which can help consumers make purchasing decisions.